2019
DOI: 10.1103/physrevb.100.075152
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation in the vicinity of Fermi surface hot spots

Abstract: Spatially inhomogeneous electronic states are expected to be key ingredients for the emergence of superconducting phases in quantum materials hosting charge-density-waves (CDWs). Prototypical materials are transition-metal dichalcogenides (TMDCs) and among them, 1T -TiSe2 exhibiting intertwined CDW and superconducting states under Cu intercalation, pressure or electrical gating. Although it has been recently proposed that the emergence of superconductivity relates to CDW fluctuations and the development of spa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 67 publications
1
16
0
Order By: Relevance
“…The simultaneous information on dynamics and structure of the surface electron density that can be obtained with HAS would also be instrumental in investigating certain aspects of high-T c materials, e.g., phase separation [132], heterogeneity [133,134] and the superstripes landscape [135][136][137] made of multiscale puddles of CDWs from 3 nm to hundreds of nm [138] controlled by doping and elastic strain [139]. The nanoscale CDW texturing has been observed in 1T-TiSe 2 [140] where by Ti self-doping the Fermi level is tuned near a Lifshitz transition in correlated multi-band systems as was predicted theoretically [141]. Moreover, it has been confirmed that the CDW texture in Sr doped Bi 2 Se 3 [142] can be manipulated by uniaxial strain to control superconductivity.…”
Section: Discussionmentioning
confidence: 99%
“…The simultaneous information on dynamics and structure of the surface electron density that can be obtained with HAS would also be instrumental in investigating certain aspects of high-T c materials, e.g., phase separation [132], heterogeneity [133,134] and the superstripes landscape [135][136][137] made of multiscale puddles of CDWs from 3 nm to hundreds of nm [138] controlled by doping and elastic strain [139]. The nanoscale CDW texturing has been observed in 1T-TiSe 2 [140] where by Ti self-doping the Fermi level is tuned near a Lifshitz transition in correlated multi-band systems as was predicted theoretically [141]. Moreover, it has been confirmed that the CDW texture in Sr doped Bi 2 Se 3 [142] can be manipulated by uniaxial strain to control superconductivity.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, a modified inner potential may be applicable for these photoelectrons. Within the three-step model, the inner potential includes a term from the material work function [33,44,45], and this is known to be strongly dependent on K dosing [46]. We speculate therefore that even though the initial states of this bulklike contribution are essentially unaffected by the dosing, the photoelectrons experience a different surface potential, and thus come out with a different effective k z .…”
Section: -5mentioning
confidence: 99%
“…Metal intercalation of 1T -TiSe 2 at certain doping concentration shows phase shift of CDW modulation across the domain walls [26,45].Cu intercalation in 1T -TiSe 2 results in incommensurate CDW phase with localized commensurate CDWs separated by domain walls at critical doping concentration [46]. T i, like Cu, is electropositive and suppresses the CDW phase.…”
Section: Resultsmentioning
confidence: 99%